Neonatal administration effects of zeranol on calves'testes and body weight (Veterinary Science, 2017)
To determine if zeranol neonatal implants (NI) produce testes alterations the same way as the estrogenic hormones,20 male Abeerden Angus calves were used divided in two gruops of equal number. The implanted group (IG) received a 24 mg zeranol NI while the control group (CG) did not get any treatment. The animals were weighed at birth and at 8 months of age, when they were castrated. The body weight gain between the IG was compared and testicular development difference between both groups was estimated through testes weight. A decrease of testes development (p0.001) and an increase in body weight gain (p0.10) were found in the IG regarding the CG. It is concluded that zeranol NI upon the testes and body gain, produces a similar effect to that of the estrogenic gonad hormones
Keywords: Seranol; Promoters; Testes